2008 Annual Reliability and Maintainability Symposium 2008
DOI: 10.1109/rams.2008.4925798
|View full text |Cite
|
Sign up to set email alerts
|

Reliability improvement of deformation tools with the Taguchi robust design

Abstract: Key Words: reliability improvement, design of experiments, Taguchi approach, renewal policy SUMMARY & CONCLUSIONSAs we are moving to more emerging global markets, one of the most important goals of a manufacturer is to improve the reliability of its products. While the reliability may be affected by many potentially factors, some factors are more important and that they have to be identified. The values of the significant factors that can improve reliability are also important to be recommended. Taguchi's robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Design of experiments is successfully applied to improve the performance of the products to specification, by reducing sensitivity to uncertain or randomly varying factors. Among a number of designed experiments methods, Taguchi's robust strategy is one of the most effective in practice and have been applied in many studies [13]. The main focuses in this method are on the product parameter selection and optimization, to ensure that the key characteristics of the product can be easily set to the target value and the variance can be minimized.…”
Section: Taguchimentioning
confidence: 99%
See 4 more Smart Citations
“…Design of experiments is successfully applied to improve the performance of the products to specification, by reducing sensitivity to uncertain or randomly varying factors. Among a number of designed experiments methods, Taguchi's robust strategy is one of the most effective in practice and have been applied in many studies [13]. The main focuses in this method are on the product parameter selection and optimization, to ensure that the key characteristics of the product can be easily set to the target value and the variance can be minimized.…”
Section: Taguchimentioning
confidence: 99%
“…It was shown that controlling and adjusting the noise factor is very costly. Thus, the objective of the Taguchi approach is to find the right settings of control factors to minimize the noise factors [13,14]. Taguchi analyzed the variation of experiments using different definitions of signal-to-noise ratio (S/N).…”
Section: Taguchimentioning
confidence: 99%
See 3 more Smart Citations